AB1368-HPR ENHANCED ROLE OF NURSES AND OTHER HEALTHCARE PROFESSIONALS (HCPS) IN THE CARE OF RHEUMATOID ARTHRITIS AND ASSOCIATED COMORBIDITIES. (June 2019) - Kent, Alison; Gabay, Cem; Geenen, Rinie; Gouni-Berthold, Ioanna; Hoogen, Frank van den; Klareskog, Lars; Ǿstergaard, Mikkel; Pavelka, Karel; Polido-Pereira, Joaquim; Semb, Anne Grete; Skld, Magnus; Balsa, Alejandro; et al.
Abstract : Background: Long-term morbidity and mortality in patients with rheumatoid arthritis (RA) are increased (1) due to the increased risk of comorbidities including cardiovascular disease (40-70% incidence (2) ; 5-12.9% prevalence (3) ), diabetes (IR of 8.6 per 1000 person-years (4) ; 20% (5) ), interstitial lung disease (7.7% (6) ; up to 60% (interstitial lung abnormalities in early RA) (7) ) and depression (up to 200% (8) ; 16.8% (9) ). In addition to differing health care delivery systems throughout Europe, there is also variability in the roles and responsibilities of healthcare professionals (HCPs) across and within countries (10) . Objectives: This study aimed to identify good practices within the roles of HCPs in the care of RA and associated comorbidities and to understand how these practices may be implemented in other centres. Methods: This study interviewed multidisciplinary teams at 12 selected specialist centres across Europe (1 centre per country) and examples of HCPs who had expanded roles and responsibilities were identified. Further, the questions whether these practices improved quality of care and could be implemented in other centres were addressed. Results: This Europe-wide study identified good practice examples of enhanced roles and responsibilities for HCPs such as nurses, physiotherapists, occupational therapists and podiatrists that varied with different categories of patients and their corresponding needs. The scope and depth of extended roles also varied between different countries and health systems. Examples included: Conclusion: Expanding the roles of HCP team members can help broaden perspectives on healthcare delivery, relieve the burden put on specialists and enable the provision of well-rounded, patient-centred holistic care that may improve quality of life for patients with RA, especially related to their associated comorbidities. References: [1] Dougados, et al. Ann Rheum Dis 2014;73:62-68 [2] Holmquist M, et al. Ann Rheum Dis 2017;76:1642-47 [3] Van Halm, et al. Ann Rheum Dis 2009; 68(9) :1395-1400 [4] Solomon D, et al. Ann Rheum Dis 2010; 69(12): 2114-7 [5] Albrecht K, et al. Rheum 2018; 57(2):329-336 [6] Bongartz, et al. Arthritis Rheum 2010; 62(6):1583-1591 [7] Reynisdottir, et al. Arthritis Rheum 2014; 66, 31-39 [8] Sheehy, et al. Rheum 2006; 45(11):1325-1327 [9] Matcham, et al. Rheumatology 2013; 52:2136-21481; 53(8):1491-1496 Disclosures: Most authors have received funding from the industry including Sanofi Genzyme who solely funded this study Disclosure of Interests: Alison Kent: None declared, Cem Gabay Grant/research support from: Roche, Pfizer, AB2 Bio Ltd, Consultant for: Roche, Pfizer, Lilly, AbbVie, Sanofi, Regeneron, Bristol-Myers Squibb, Novartis, UCB, AB2 Bio Ltd, Debiopharm, Rinie Geenen: None declared, Ioanna Gouni-Berthold: None declared, Frank van den Hoogen: None declared, Lars Klareskog Grant/research support from: Yes, but not for the presented study., Mikkel Ǿstergaard Grant/research support from: Abbvie, Celgene, Centocor, Merck, Novartis, Consultant for: Abbvie, BMS, Boehringer-Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo, Orion, Pfizer, Regeneron, Roche, and UCB, Speakers bureau: Abbvie, BMS, Boehringer-Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo, Orion, Pfizer, Regeneron, Roche, and UCB, Karel Pavelka: None declared, Joaquim Polido-Pereira: None declared, Anne Grete Semb: None declared, Magnus Skld: None declared, Alejandro Balsa Grant/research support from: Abbvie, Pfizer, Novartis, BMS, Nordic, Sanofi, Consultant for: Abbvie, Pfizer, Novartis, BMS, Nordic, Sanofi, Sandoz, Lilly, Paid instructor for: Pfizer, Speakers bureau: Pfizer, Novartis, UCB, Nordic, Sanofi, Sandoz, Lilly, Neil Betteridge Consultant for: Amgen, Eli Lilly, Grunenthal, GSK, Heart Valve Voice, Janssen, Roche, Sanofi Genzyme and Sanofi Regeneron, Speakers bureau: Amgen, Eli Lilly, Grunenthal, GSK, Heart Valve Voice, Janssen, Roche, Sanofi Genzyme and Sanofi Regeneron, Maya Buch Grant/research support from: Pfizer LTD, UCB, Consultant for: AbbVie, Eli Lilly, EMD Serono, Pfizer Ltd., Sanofi, maxime dougados Grant/research support from: Eli Lilly and Company, Pfizer, AbbVie, and UCB Pharma, Consultant for: Eli Lilly and Company, Pfizer, AbbVie, and UCB Pharma, Patrick Durez Speakers bureau: Bristol-Myers Squibb, Eli Lilly, Sanofi, Celltrion, Ennio Favalli: None declared, Guillaume Favier: None declared, Tore K. Kvien Grant/research support from: AbbVie, BMS, MSD, Pfizer, Roche and UCB., Consultant for: AbbVie, Biogen, BMS, Boehringer Ingelheim, Celgene, Celltrion, Eli Lilly, Hospira, Merck-Serono, MSD, Novartis, Oktal, Orion Pharma, Pfizer, Roche, Sandoz, Sanofi, Mylan and UCB, Speakers bureau: AbbVie, Biogen, BMS, Boehringer Ingelheim, Celgene, Celltrion, Eli Lilly, Hospira, Merck-Serono, MSD, Novartis, Oktal, Orion Pharma, Pfizer, Roche, Sandoz, Sanofi and UCB